Technology -Based Business Idea Blueprint SNS Sdn. Bhd. / Siti Nadia Shifudin - Shifudin, Siti Nadia (2020)
SNS Sdn. Bhd. is located at Johor and has been operated since 8th December 2019. It is a sole proprietorship company. Its focus is selling home appliance technology-based product, such as television, air-conditioner and many more. However, SNS Sdn Bhd main product is De‟ Brush